Bay Leaf (Syzygium Polyanthum) Extract Effect on IL-10 and IL-6 Gene Expression in Traumatic Ulcer - Shafia, Arina; Trisnadi, Setyo; Putra, Agung (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
The aims of this research is to prove the effect of bay leaf extract gel on IL-10 and IL-6 gene expression in traumatic ulcers. The research method using In vivo experimental study with a randomized posttest-only control group design. The total sample was 24 male Wistar rats, divided into four groups. Group K1 (given base gel), group K2 (given Kenalog in Orabase), group K3 (10% bay leaf extract gel), and group K4 (15% bay leaf extract gel) were given treatment for 5 days. IL-6 and IL-10 levels were tested using the One-Way Anova test, followed by the Tamhane Post Hoc test. This study revealed that there was a difference in IL-6 levels in the K4 group compared to the K1 group sig. (p = 0.007) and a significant difference in IL-10 levels in the K4 group compared to the K1 group. (p = 0.003) after being given topical treatment with bay leaf extract gel. The conclusion of this research is treatment with 15% bay leaf gel extract (Syzygium polyanthum) was proven to significantly increase IL-10 gene expression and decrease IL-6 gene expression in Wistar rats model of traumatic ulcers.